IN SILICO STUDIES OF THE SECONDARY METABOLITES OF SOLANUM TORVUM SW. FOR THEIR ANTIASTHMATIC ACTIVITY - R., Soorya; P., Dhamodaran; R., Rajesh Kumar; B., Duraisamy (International Journal of Current Pharmaceutical Research, 2017)
Objective: Solanum torvum Sw., Family: Solanaceae, commonly known as Turkey Berry is used by the traditional tribes for the treatment of cold, cough, tuberculosis, hepatotoxicity, cancer, etc. The action of the plant towards the treatment of these diseases has been proven except for asthma. The present study is to prove the antiasthmatic activity of methanolic extract and the secondary metabolites of Solanum torvum Sw using in silico docking studies in compare to reference standard Dexamethasone, a synthetic cortisone derivative. Methods: The GC-MS analysis of the dried methanolic extract of the dried fruits of Solanum torvum Sw. and the total saponin fraction has been carried out to know the important moieties that are responsible for the antiasthmatic activity. Results: The results from the docking studies showed that the compounds Cholesta-5,7,9-(11)-trien-3-ol,4,4-dimethyl, (3Ã¡); Lanosta-7,9-(11),20-triene-3Î±, 18-diol, diacetate and Cholestan-26-oic acid,3,7,12,24-tetrakis (acetyloxy), methyl ester, (3Ã ,5Ã¡,7Ã ,12Ã ) were found to have significant scores of-6.8,-6.9 and-6.9 respectively towards Glucocorticoid receptor protein (Gr), (PDB id: 4UDC) which is very similar to the affinity of the standard (-7.1). These compounds passed the drug-likeness test. A modification in the structure can be brought, which makes the compounds more potent. The compounds 9, 12-Octadecadienoic acid, ethyl ester; Hexadecanoic acid, ethyl ester; 9-Octadecenoic acid (Z), methyl ester; Oxacycloheptadec-8-en-2-one, (8Z) have passed the Blood Brain Barrier (BBB) filter of the drug-likeness test. Conclusion: The antiasthmatic activity of the drug may be due to the similarity with the structure of Dexamethasone. Further research can be carried out in order to improve the clinical significance of these extracts and its metabolites.